Satysfakcja klienta jako miernik efektywności systemu zarządzania jakością - Giemza, Mariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
An organization depends on its customers. Because of that it should meet and get to know all customers' needs and expectations. The growing number of customers is a very positive indicator of effectivity of quality management system. According to it organizations should check customers satisfaction rate. To achieve it organizations may use direct and indirect methods. The issue of customers satisfaction analysis in Polish organizations is an object of activity of science. The most common technique of customer's satisfaction analysing is a questionnaire technique. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 186-192